Diet of the Neotropic Cormorant Phalacrocorax olivaceus at West Chubut, Patagonia, Argentina - Casaux, Ricardo Jorge (2009)
A total of 124 pellets (regurgitated casts) produced by the Neotropic Cormorant (Phalacrocorax olivaceus) were collected monthly between January 2004 and November 2005 from a roosting site at Rosario Lake Chubut, Patagonia, Argentina. Analyses of the samples showed that fish were the most frequent and important prey by number, followed by crustaceans and molluscs. The three fish species inhabiting Rosario Lake were represented in the diet which suggests that this bird is a generalist feeder. However, cormorants positively selected for Patagonian Silverside and Rainbow Trout, which might be related to their foraging strategy and/or to the conspicuousness of potential prey. The estimated annual fish intake by cormorants at Rosario Lake ranged between 2.3-3.7 tons of fish or 16,000-26,000 individuals. The impact produced by the Neotropic Cormorant on recreational fish resources and local fish farms appears negligible.